Gold Mining and Political Struggles for Access in Banyuwangi, East Java - Indah Surya Wardhani; Devy Dhian Cahyati (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This article explores how the materiality of natural resources influences social movements. Applying a relational paradigm and new materialism approach, this article explores the materiality of gold as a vital element of actor-network linkages, organisation, framing mechanisms, and recruitment. The transformation of gold from an ore into a mechanism for commodification reflects the interactions between capital holders, scientists, political actors, and legislators. This sociomaterial formation has limited residents' access to such resources as gold, water, land, wood, and clean air, and this momentum has given rise to a social movement in opposition to gold mining activities. This article shows that social movements are not monolithic, but rather dynamic movements that consist of various actors, issues, narratives, and strategies. This study focuses on the anti-mining movement in Tumpang Pitu, Banyuwangi, East Java, and its two decades of struggle to illustrate how the formation, networking, fragmentation, and evolution of social movements is influenced by their materiality (in this case, gold). This article finds that the commodification of gold influences movements' repertoires. This offers an alternative explanation for social movements, which have long been dominated by an actor–structure approach that views social movements as linear, monolithic, and constant collective actions that respond to marginalisation and injustice.